Depletion of Tissue-Specific Ion Transporters Causes Differential Expression of PRL Targets in Response to Increased Levels of Endogenous PRL - Shu, Tingting; Shu, Yuqin; Gao, Yanping; Jin, Xia; He, Jiangyan; Zhai, Gang; Yin, Zhan (Frontiers in Endocrinology, 2018)
Prolactin (PRL) has been considered a key regulator of ion uptake in zebrafish. The genes slc12a10.2 and slc12a3, which are Na+ and chloride Cl− co-transporters, have been reported to be regulated by PRL in freshwater fish. The integrative network of PRL signaling dissected from the knockout of tissue-specific downstream PRL ion transporters remains poor. In the present study, zebrafish models with increased endogenous levels of PRL were generated through the knockout of slc12a10.2 or slc12a3, and the developmental consequences were analyzed. The increased levels of pituitary PRL were observed in both slc12a10.2- and slc12a3-deficient fish. Unlike the slc12a3-deficient fish, which could survive to adulthood, the slc12a10.2-deficient fish began to die at 9 days post-fertilization (dpf) and did not survive beyond 17 dpf. This survival defect is a result of defective Cl− uptake in this mutant, indicating that Slc12a10.2 plays an essential role in Cl− uptake. Intriguingly, compared to the levels in control fish, no significant differences in the levels of Na+ in the body were observed in slc12a10.2- or slc12a3-deficient zebrafish. The upregulations of the PRL downstream transporters, slc9a3.2, slc12a10.2, and atp1a1a.5 were observed in slc12a3-deficient fish in both the gills/skin and the pronephric duct. However, this type of response was not observed in the pronephric duct of slc12a10.2-deficient fish, except under Na+-deprived conditions. Our results show that PRL is susceptible to deficiencies in downstream ion transporters. Moreover, both the gills/skin and pronephric duct show differential expression of downstream PRL targets in response to increased levels of pituitary PRL caused by the depletion of tissue-specific ion transporters.